Kesahihan Hadis dalam Paradigma Bayani, Burhani, dan ‘Irfani: Telaah atas Epistemologi al-Ghazali - Jannah, Safri Nur; Al Anwari, Ahmad Ubaidillah Ma'sum (Al-Qudwah, 2025)
The issue of hadith authenticity remains a pivotal subject within both classical and contemporary Islamic scholarship. The lack of standardized methods of transmission during the early Islamic period, coupled with the extensive misuse of hadiths for political and ideological objectives, has introduced significant challenges in assessing their validity. A prominent figure frequently examined in this context is Abu Hamid al-Ghazali, particularly regarding his approach to hadith transmission in Ihya’ ‘Ulum al-Din, which often omits a complete chain of narration (sanad). Critics among hadith scholars contend that al-Ghazali incorporated weak (dha‘if) or even fabricated (maudhu‘) traditions, whereas Sufi scholars and intellectuals defend his methodology, highlighting his spiritual perspective and comprehensive moral framework. This study utilizes a qualitative methodology grounded in library research, employing a descriptive-analytical approach. The data are derived from both primary and secondary sources pertaining to al-Ghazali’s thought, as well as classical and contemporary ulūm al-ḥadīth literature. The analysis is framed within the epistemological constructs of bayani, burhani, and irfani, as articulated by Abid al-Jabiri. The findings reveal that al-Ghazali did not reject scientific methods in hadith studies; rather, he integrated these methods with spiritual dimensions. His adherence to the principles of sanad and the moral integrity of transmitters exemplifies the bayani approach; his rational evaluation of transmission validity reflects the burhani dimension; and his acceptance of spiritual intuition (kashf and liqā’ al-nabi) as a means of verification—provided it does not contradict Sharia—embodies the irfani approach. Consequently, al-Ghazali’s conception of hadith authenticity constitutes an epistemological synthesis of scientific objectivism and spiritual subjectivism.Abstrak: Problematika autentisitas hadis merupakan isu sentral dalam kajian Islam klasik maupun kontemporer. Tidak adanya standarisasi periwayatan pada masa awal Islam serta maraknya penyalahgunaan hadis untuk kepentingan politik dan ideologis menimbulkan kompleksitas dalam menentukan validitas hadis. Salah satu tokoh yang kerap menjadi sorotan dalam isu ini adalah Abu Hamid al-Ghazali, terutama terkait metode periwayatan hadis dalam Ihya’ ‘Ulum al-Din yang tidak selalu mencantumkan sanad secara lengkap. Kritik dari kalangan ahli hadis menuduh al-Ghazali memasukkan hadis dha‘if bahkan maudhu‘, sementara kalangan sufi dan intelektual membelanya dengan menekankan pendekatan spiritual dan moralitas substansial yang diusungnya. Penelitian ini menggunakan metode kualitatif berbasis studi pustaka dengan pendekatan deskriptif-analitis. Data diperoleh dari karya-karya primer dan sekunder terkait pemikiran al-Ghazali serta literatur ulūm al-ḥadīṡklasik dan modern. Analisis dilakukan dengan menggunakan kerangka epistemologi bayani, burhani, dan irfani sebagaimana dirumuskan oleh Abid al-Jabiri. Hasil penelitian menunjukkan bahwa al-Ghazali tidak menolak metode ilmiah dalam kajian hadis, melainkan mengintegrasikannya dengan dimensi spiritual. Komitmennya terhadap prinsip sanad dan keadilan perawi mencerminkan pendekatan bayani; rasionalisasi terhadap validitas riwayat memperlihatkan aspek burhani; sedangkan penerimaan terhadap intuisi rohani (kashf dan liqā’ al-nabi) sebagai sarana verifikasi selama tidak bertentangan dengan syariat—menunjukkan pendekatan irfani. Berdasarkan hal di atas, konstruksi kesahihan hadis dalam pandangan al-Ghazali merupakan sintesis epistemologis antara objektivisme ilmiah dan subjektivisme spiritual.